Hydrophilic modification method of UHMWPE (Ultra High Molecular Weight Polyethylene) ultrathin film

By using extremely dilute polyvinyl alcohol solution for dip coating modification, the challenge of hydrophilic modification of the UHMWPE ultra-thin film surface was solved, and the integrity and hydrophilicity of the film were improved, which significantly reduced the water contact angle.

CN119463261AActive Publication Date: 2025-02-18SICHUAN UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411607306.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-18
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

The prior art is difficult to effectively modify the surface of UHMWPE ultrathin films, especially in the macroscopic damage of ultrathin films.

Method used

The UHMWPE ultra-thin film surface was hydrophilicly modified by dip coating method to ensure the flexibility and effectiveness of the modification process.

Benefits of technology

The hydrophilicity improvement of the UHMWPE ultra-thin film surface is achieved, ensuring the integrity of the film, and significantly reducing the water contact angle, making the film change from hydrophobicity to hydrophilicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463261A_ABST
    Figure CN119463261A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of high polymer materials, in particular to a hydrophilic modification method of a UHMWPE (Ultra High Molecular Weight Polyethylene) ultrathin film. According to the hydrophilic modification method, the extremely dilute polyvinyl alcohol solution is used, the surface of the UHMWPE ultrathin film is subjected to hydrophilic modification through a dip-coating method, the integrity of the UHMWPE ultrathin film cannot be damaged, the overall modification of the UHMWPE ultrathin film can be achieved, the water contact angle can be reduced by 40 degrees or above when the weight fraction of polyvinyl alcohol in the polyvinyl alcohol solution is only 0.0001%, and the water contact angle can be reduced by 30 degrees or above. The UHMWPE film is changed into a hydrophilic surface from a hydrophobic surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a method for hydrophilic modification of an ultra-thin UHMWPE film. Background Art

[0002] In some cases, polyethylene (PE) products require surface modification before use. Such modifications can be divided into three major categories: chemical, physical, and polymer processing. Physical methods include UV, plasma, corona, or flame treatments, which have the advantage of negligible changes to intrinsic properties. However, such physical modifications can also be superficial and susceptible to environmental degradation, resulting in attenuation of the modification effect. Chemical methods often require chemical reagents or catalysts to oxidize, sulfonate, aminate, graft, or crosslink the PE surface to introduce various functional groups to improve hydrophilicity, antimicrobial properties, antifouling properties, etc. Polymer processing methods mainly involve modifying the polyethylene surface through polymer blending, coextrusion, and compounding. This approach can achieve a variety of surface modification goals and has scalable production capabilities, but may also be affected by increased costs or operational complexity. In addition to chemical treatments, chemical reactions may also occur during physical and processing modifications. In addition to chemical treatments, chemical reactions may also occur during physical and processing modifications. Due to the lower dissociation energy of CC bonds to CH bonds (80 kCal / mol vs. 100 kCal / mol), the carbon backbone cleavage almost inevitably leads to chain scission. This modification then leads to a decrease in the molecular weight and mechanical robustness of the PE product.

[0003] At present, there are few studies on the polar modification of the surface of ultra-high molecular weight polyethylene (UHMWPE) ultra-thin film. In the prior art, the general modification method for common block, rod or thin sheet polyolefin materials is to introduce free radicals: for example, plasma treatment, ultraviolet irradiation, electrochemical ion generation method, grafting reaction, etc. However, for ultra-high molecular weight polyethylene ultra-thin film, if one of the above modification methods is carried out to destroy the surface molecular chain to introduce free radicals and then graft polar functional groups or provide redox chemical sites, based on the ultra-high molecular weight polyethylene ultra-thin film previously prepared by the applicant (CN 113263747B, a large-area ultra-high molecular weight polyethylene ultra-thin film and its preparation method), because its thickness of less than 200nm is equivalent to the characteristic size of several or even a single shish-kebab inside, this means macroscopic damage to the entire ultra-thin film.

[0004] Therefore, a gentle and effective modification method is needed to modify the UHMWPE ultra-thin film to ensure the integrity of the ultra-thin film. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a method for hydrophilic modification of a UHMWPE ultra-thin film, which uses an extremely dilute polyvinyl alcohol solution to hydrophilically modify the surface of the UHMWPE ultra-thin film by a dip coating method.

[0006] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0007] A method for hydrophilic modification of a UHMWPE ultra-thin film comprises the following steps:

[0008] S1: preparing a very dilute polyvinyl alcohol solution;

[0009] S2: using the polyvinyl alcohol solution prepared in step S1 to perform surface hydrophilic modification on the UHMWPE ultra-thin film by dip coating.

[0010] Further, the extremely dilute polyvinyl alcohol solution refers to a polyvinyl alcohol solution with a mass concentration of 0.0001-10%. The mass concentration of 0.0001-10% may include any individual value within this numerical range, such as but not limited to 0.0001%, 0.001%, 0.01%, 0.1%, 0.5%, 10%, etc., and any range between the individual values, such as 0.0001-0.1%, 0.0001-0.01%, etc.

[0011] Furthermore, the polyvinyl alcohol solution is prepared as follows: polyvinyl alcohol and deionized water are weighed according to the required mass concentration, mixed, and heated to dissolve.

[0012] Furthermore, the heating temperature is 80-90°C.

[0013] Furthermore, the surface hydrophilic modification in step S2 includes the following operation steps: completely immersing the UHMWPE ultra-thin film in the polyvinyl alcohol solution, maintaining it at 40-80° C. for 8-15 hours, and then drying it.

[0014] Furthermore, the immersion can be performed on any suitable apparatus. For example, it can be performed in a polytetrafluoroethylene plate with a groove. In this example, the UHMWPE ultra-thin film can be placed in a groove opened on the polytetrafluoroethylene plate, and a very dilute polyvinyl alcohol solution can be slowly poured into the groove to immerse the UHMWPE ultra-thin film, and the polytetrafluoroethylene plate as a whole is kept at a constant temperature for 8 to 15 hours, and then the UHMWPE ultra-thin film is dried.

[0015] Furthermore, the molecular weight of the UHMWPE is 1 million to 10 million.

[0016] Furthermore, the thickness of the UHMWPE ultra-thin film is 70-500 nanometers.

[0017] Furthermore, the thickness of the UHMWPE ultra-thin film is between 70 and 200 nanometers.

[0018] The UHMWPE ultra-thin film as described herein can be commercially available, or the ultra-thin film can be prepared from UHMWPE itself. The method for preparing an ultra-thin film from UHMWPE is known to those skilled in the art, for example, the UHMWPE ultra-thin film as described herein can be prepared using the method disclosed in the invention patent CN113263747B, or, for example, ultra-high molecular weight polyethylene and a solvent can be used to form a suspension by stirring and melt blending, and then a gel film is formed by banburying and high-temperature pressing, and then a film with a thickness of 70-500 nanometers is formed by multi-step stretching, annealing and extraction.

[0019] Another object of the present invention is to provide a surface hydrophilically modified UHMWPE ultra-thin film, which is prepared by the hydrophilic modification method as described herein.

[0020] Advantageous Effects of the Invention

[0021] The UHMWPE ultra-thin film hydrophilic modification method of the present invention comprises preparing an extremely dilute polyvinyl alcohol solution, and hydrophilically modifying the surface of the UHMWPE ultra-thin film by a dip coating method, and the integrity of the UHMWPE ultra-thin film is ensured by a gentle and effective modification method;

[0022] The UHMWPE ultra-thin film hydrophilic modification method of the present invention benefits from the ultra-thin size of the UHMWPE ultra-thin film. When the surface of the UHMWPE ultra-thin film is modified, it is almost the entire UHMWPE ultra-thin film is modified.

[0023] The UHMWPE ultra-thin film hydrophilic modification method of the present invention performs hydrophilic modification on the surface of the UHMWPE ultra-thin film by dip coating, so that polyvinyl alcohol can enter the UHMWPE ultra-thin film to improve the hydrophilicity of its surface;

[0024] The method for hydrophilic modification of UHMWPE ultra-thin film of the present invention can reduce the water contact angle by more than 40° when the weight fraction of polyvinyl alcohol in the polyvinyl alcohol solution is only 0.0001%, so that the UHMWPE film changes from a hydrophobic surface to a hydrophilic surface; as the concentration of the polyvinyl alcohol solution used for dipping the UHMWPE ultra-thin film increases, the water contact angle on the surface of the UHMWPE ultra-thin film gradually decreases, and its hydrophilicity also gradually increases.

[0025] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1These are photos of water contact angles corresponding to the UHMWPE ultra-thin films after dip-coating with different PVA concentrations as described in the embodiments of the present invention.

[0027] Figure 2 These are SEM photos of the UHMWPE ultra-thin films after dip-coating with different PVA concentrations as described in the embodiments of the present invention.

[0028] Figure 3 These are AFM photos of the surface of the UHMWPE ultra-thin film after dip-coating with PVA of different concentrations as described in the embodiments of the present invention.

[0029] Figure 4 XRD patterns of UHMWPE ultra-thin films modified with PVA at different concentrations.

[0030] Figure 5 This is a SEM image of the UHMWPE ultrathin film treated with plasma.

[0031] Figure 6 This is the energy spectrum of UHMWPE ultra-thin film treated with plasma.

[0032] Figure 7 This is the preparation flow chart of PVA modified UHMWPE ultra-thin film.

[0033] Figure 8 These are SEM images of three membrane materials modified by 0.01% PVA.

[0034] Fig. 9 The WCA diagram of three membrane materials after modification with 0.01% PVA.

[0035] Fig.10 These are the SEM and WCA images of UHMWPE ultra-thin film modified by chitosan. DETAILED DESCRIPTION

[0036] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0037] The UHMWPE ultra-thin film is an ultra-thin film with a thickness of 200 nanometers made of ultra-high molecular weight polyethylene. It is prepared by conventional methods known in the art. For example, ultra-high molecular weight polyethylene and a solvent can be used to form a suspension by stirring and melt blending, and then a gel film is formed by mixing and high-temperature pressing. After multiple steps of stretching, annealing and extraction, a film with a thickness of 200 nanometers is formed.

[0038] Example

[0039] A method for hydrophilic modification of a UHMWPE ultra-thin film, comprising:

[0040] S1: preparing a very dilute polyvinyl alcohol solution;

[0041] S2: The surface hydrophilic modification of the UHMWPE ultra-thin film was carried out by dip coating using the extremely dilute polyvinyl alcohol solution prepared in S1.

[0042] In this embodiment, the extremely dilute polyvinyl alcohol solution is prepared as follows:

[0043] The PVA solution was prepared by a dissolution method, wherein: the solvent was deionized water and the solute was PVA;

[0044] The preparation process is as follows: using an electronic balance to weigh PVA raw materials (weighed according to the weight fraction of the solution 0.1%, 0.01%, 0.001%, 0.1%, 0.5%, 10%) and deionized water;

[0045] Put the weighed raw materials into a three-necked flask, then add deionized water, and fully heat them in an oil bath. Set the temperature to 95°C and stir magnetically during the heating process to facilitate the full dissolution of PVA. After it is fully dissolved, take it out and cool it for later use;

[0046] In this embodiment, the surface of the UHMWPE ultra-thin film is hydrophilically modified by dip coating using an extremely dilute polyvinyl alcohol solution:

[0047] The UHMWPE ultra-thin film is placed in a square polytetrafluoroethylene plate with a groove, and then the extremely dilute PVA solution prepared above is slowly poured into the groove with the UHMWPE film, so that the PVA dilute solution can completely immerse the UHMWPE ultra-thin film;

[0048] The whole device was placed on a hot table and kept at a constant temperature of 60°C for 12 hours to allow the PVA solution to fully infiltrate the UHMWPE. The solvent (water) contained in the surface of the membrane was then dried in an oven. In this way, the PVA could enter the PE membrane and improve its surface hydrophilicity.

[0049] The water contact angle of the hydrophilic modified UHMWPE ultra-thin film prepared in this embodiment was tested, and the results are shown in Tables 1 and Figure 1-3 As shown:

[0050] Table 1: Water contact angles of UHMWPE after dip coating with different PVA concentrations

[0051] PVA(%) 10wt 5wt 0.5wt 0.1wt 0.01wt 0.001wt 0.0001wt 0wt WCA(°) 42 53 60 66 70 73 82 125

[0052] The water contact angle of UHMWPE without PVA modification is 125°, while the water contact angle of UHMWPE after PVA dipping is changed to 82° at a concentration of only 0.0001%, which is reduced by more than 40°, and the UHMWPE membrane is changed from a hydrophobic surface to a hydrophilic surface; as the concentration of the PVA solution used for dipping the UHMWPE membrane increases, the water contact angle of the UHMWPE membrane surface gradually decreases, and its hydrophilicity gradually increases;

[0053] Figure 1 The water contact angle photos corresponding to the UHMWPE ultra-thin films after dip coating with different PVA concentrations are shown;

[0054] Figure 2 The SEM images of UHMWPE ultrathin films after dip coating with different PVA concentrations are shown;

[0055] Figure 3 Shows the surface AFM images of UHMWPE ultrathin films after dip coating with different PVA concentrations.

[0056] Figure 4 The XRD patterns of UHMWPE ultrathin films modified with PVA at different concentrations are shown. As shown in the figure, compared with the XRD patterns of pure PE and pure PVA, the XRD patterns of PVA-PE composite films with different loadings show that different loadings of PVA will not change the crystalline structure of the PE film itself, and the characteristic peaks of PE are displayed on the (110) and (200) planes of PE; the low-loading composite film does not show obvious PVA characteristic peaks, which is because the PVA loading is too low and the signal is too weak, which is blocked by the PE signal.

[0057] Comparative Example 1

[0058] According to the conventional method known in the art, plasma-treated UHMWPE ultra-thin film samples were prepared, and it was found that the fibers on the surface of the samples were significantly deformed. Figure 5 As shown, Figure 5 -The left picture is a scanning electron microscope picture of pure PE. Figure 5 -The right picture shows the PE film after plasma treatment. It can be seen that the fiber bundles on the surface of the untreated film are smooth, non-adhesive and thin; the fiber bundles after plasma treatment become rough, thicker and stick together. This is due to the introduction of C=O double bonds, which leads to partial oxidation of polyethylene; although the hydrophilicity of the polyethylene film surface after plasma treatment has changed greatly, the structure of polyethylene has changed, resulting in reduced mechanical properties of the ultra-thin polyethylene film, brittle and easy to break.

[0059] Comparative Example 2

[0060] According to the example, three samples of thick PE film materials (including two thick PE films and one PTFE film. The 1.8 μm PE is a biaxially stretched polyethylene film with a stretch ratio of 9x9=81; the 16 μm PE is a commercial polyethylene battery separator, manufactured by Enjie; and the 30 μm PTFE film is manufactured by Taizhou Chenguang Plastic Industry Co., Ltd., model CG003) were treated with 0.01% PVA by dip coating. It was found that the fibers on the sample surface all had certain deformation. Figure 8 As shown, Figure 8 -a is the scanning electron microscope image of 2.5μm PE film, Figure 8 -d is the SEM image of the 2.5μm PE film after modification. Figure 8 -b is a scanning electron microscope image of a 16μm commercial PE battery separator. Figure 8 -e is the SEM image of the 16μm commercial PE battery separator after modification. Figure 8 -c is the scanning electron microscope image of 30μm PTFE membrane, Figure 8 -f is a scanning electron microscope image of the 30μm PTFE membrane after modification. For the 2.5μm PE membrane and the 16μm PE membrane, it can be seen that the surface fiber bundles are smooth, non-adhesive, and thin when not modified. After the modification, the fiber bundle surface becomes rough, the fiber bundles become thicker and adhere together, and for the 16μm PE membrane, the phenomenon of less pore blockage is obvious. Since the 30μm PTFE membrane has no pores, the surface morphology is almost unchanged before and after the modification. Fig. 9 As shown in the figure, after being modified with 0.01% PVA, the water contact angles of the three thick film samples all became smaller, but the degree of change was not large, and the hydrophilic modification effect was not obvious. This shows that the hydrophilic modification effect of PVA on thick films is not as good as that of ultra-thin films.

[0061] Comparative Example 3

[0062] According to the method described in the examples, the UHMWPE samples were treated by dip coating with chitosan solution, such as Fig.10 As shown, it can be seen that the surface morphology and water contact angle of the treated UHMWPE sample are almost unchanged, and the hydrophilic modification effect is very poor.

[0063] It should be noted that the preferred embodiments of the present invention are given in the specification and drawings of the present invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not used as additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all regarded as the scope of the present invention; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.

Claims

1. A method for hydrophilic modification of UHMWPE ultra-thin film, characterized in that: The following steps are involved: S1: preparing a polyvinyl alcohol solution with a mass concentration of 0.0001-10%; S2: using the polyvinyl alcohol solution prepared in step S1 to perform surface hydrophilic modification on the UHMWPE ultra-thin film by dip coating.

2. The hydrophilic modification method according to claim 1, characterized in that: The polyvinyl alcohol solution is prepared as follows: polyvinyl alcohol and deionized water are weighed according to the required mass concentration, mixed, and heated to dissolve.

3. The hydrophilic modification method according to claim 2, characterized in that: The heating temperature is 80-90°C.

4. The hydrophilic modification method according to claim 1, characterized in that: The surface hydrophilic modification in step S2 includes the following steps: completely immersing the UHMWPE ultra-thin film in the polyvinyl alcohol solution, maintaining it at 40-80° C. for 8-15 hours, and then drying it.

5. The hydrophilic modification method according to claim 4, characterized in that: The immersion was performed in a polytetrafluoroethylene plate having grooves.

6. The hydrophilic modification method according to claim 1, characterized in that: The molecular weight of the UHMWPE is 1 million to 10 million.

7. The hydrophilic modification method according to claim 1, characterized in that: The thickness of the UHMWPE ultra-thin film is 70-500 nanometers.

8. A surface hydrophilically modified UHMWPE ultra-thin film, prepared by the method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • A large-area ultra-high molecular weight polyethylene ultrafilm and its preparation method

    CN113263747B

  • Method for improving hydrophilicity of ultra-high molecular weight polyethylene product

    CN113121861A

  • Hydrophilic modified ultra-high molecular weight polyethylene fiber and preparation method thereof

    CN118563567A

  • Method for hydrophilic modification of ultrahigh molecular weight polyethylene microporous membrane surface

    CN1640533A

  • High barrier recyclable laminated film and preparation method thereof

    US12097686B1